Temperature dependency in motor skill learning - Immink, M. A.; Wright, D. L.; Barnes, W. S. (Journal of Motor Behavior, 2012)
The present study investigated the role of temperature as a contextual condition for motor skill learning. Precision grip task training occurred while forearm cutaneous temperature was either heated (40-45 °C) or cooled (10-15 °C). At test, temperature was either reinstated or changed. Performance was comparable between training conditions while at test, temperature changes decreased accuracy, especially after hot training conditions. After cold training, temperature change deficits were only evident when concurrent force feedback was presented. These findings are the first evidence of localized temperature dependency in motor skill learning in humans. Results are not entirely accounted for by a context-dependent memory explanation and appear to represent an interaction of neuromuscular and sensory processes with the temperature present during training and test.